Biodiversity in Agroforestry Systems: A Case Study in Homegardens of Gulmi and Palpa Districts, Western Nepal - Pokhrel, Chandra P.; Timilsina, Arbindra; Khanal, Rajib; Ando, Kazuo; Yadav, Ram Kailash P. (Journal of Institute of Science and Technology, 2015)
Homegardens are important part of an agroecosystem, which has long been practiced in Nepalese farming systems but poorly studied. This study identified the diversity of plant species of 73 homegardens of Hastichaur Village Development Committee (VDC), Gulmi district and 43 homegardens of Siddheshwor VDC, Palpa district. A total of 110 different plant species were recorded within three layers i.e. top layer (3-15m), middle layer (1-3 m) and ground layer (up to 1m). Species richness in the Hastichaur was higher (90) than Siddheshwor (73) VDC; in contrast species evenness was higher in Siddheshwor than Hastichaur. The bigger sized homegardens (average size was 250 m²) belong to Brahmin and Chhetri and recorded the highest plant species diversity (1.791) and species richness (90). In contrast, smaller sized homegardens (average size was 80 m²) belong to Dalit community and recorded the lowest diversity (1.696) and species richness (60) of the plants. The presence of the vegetable species, Zingiber officinale and Capsicum annuum was highest (95%) in Siddheswor VDC and annuum (85%) was highest in Hastichaur VDC. The presence of medicinal plants was very low in both VDCs. The trend of plant species richness showed was as Brahmin/Chettri > Magar > Kumal > Dalit in Hastichaur and as Brahmin/Chettri > Kumal > Magar > Dalit in Siddheshwor VDCs. Journal of Institute of Science and Technology, 2015, 20(1): 87-96